Comparison of Oral Misoprostol with Conventional Oxytocics in the Management of Third Stage of Labor - hadi, hameedah (Karbala Journal of Medicine, 2019)
this paper was objective to compare oral misoprostol with conventional oxytocics in the management of the third stage of labor. this experiment was done in Department of obstetrics and gynecology at Baghdad Teaching Hospital. In controlled trials a pregnant women total number 280 were randomized into four groups, as followed: Group 1: received oral misoprostol 400 µg, followed by two doses of oral misoprostol 100 µg 4hours a part. (n=72), group 2: received intravenous infusion of oxytocin 10 IU plus oral misoprostol 400 µg ,followed by two doses of oral misoprostol 100 µg 4 hours apart.(n=62), group 3: received intravenous infusion of oxytocin 10 IU. (n=69),group 4: received intravenous infusion of 10 IU oxytocin plus intramuscular administration of methylergometrine (methergine) 0.2 mg. (n=77). The main measures,the incidence of postpartum hemorrhage and the changes in hematocrit concentration from before delivery to 24 hours postpartum in those women used oral misoprostol in management of third stage of labor with or without the use of other oxytocics. the results shows, all the patients were matched for their age, parity, body mass index, gestational age, birth weight. Mean blood loss in misoprostol group was not significantly higher than blood loss in oxytocin group and oxytocin misoprostol group, but there was statistically significant difference when compared with oxytocin-methylergometrine group. the main conclusions ,oral administrated misoprostol is as effective as conventional oxytocics in management of third stage of labor and prevention of postpartum hemorrhage with limited side effects.